Morphological and Behavioral Abnormalities Induced by Hydrogen Peroxide in Drosophila melanogaster. - Hernández-Calderón, M.L.; Gallegos-Moreno, A.; Miranda-Camacho, A.Y.; Sánchez-Jiménez, C.L.; Díaz-Barriga-Arceo, S.; Aguirre-Joya, J.A.; Torres-León, C.; Aguillón-Gutiérrez, D.R. (Biology (Basel), 2025)
Congenital developmental defects are among the postnatal consequences of early exposure to hydrogen peroxide or other teratogens that induce oxidative stress, highlighting a potential mechanistic link between oxidative stress, redox signaling, and developmental processes. This study evaluated the morphological and behavioral abnormalities induced by hydrogen peroxide in the Drosophila melanogaster model, as well as its teratogenic index. The results demonstrated that hydrogen peroxide induces morphological abnormalities in adult wings, legs, and abdomen, as well as necrosis and developmental disruptions during larval and pupal stages. A median lethal concentration (LC50) of 0.16% and a teratogenic index (TI) of 0.44 were calculated when considering anomalies at any development stage; a TI of 0.21 was obtained when considering only adult abnormalities. Regarding behavioral changes, an increase in locomotor activity was observed in both larvae and adults, with significantly greater activity recorded in adult females than in males. These findings suggest that hydrogen peroxide can induce both morphological and behavioral abnormalities in D. melanogaster, although it presents a low teratogenic index.